Literasi Keuangan melalui Kesadaran Menabung pada Anak-Anak Desa Ndeskati - Khofifah Nurandini Siregar; Maya Sari Sihombing; Widia Febrianti; Yusuf Hadijaya (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
Financial literacy is an essential skill that needs to be instilled from an early age so that the younger generation develops the ability and habit of managing money wisely. This study focuses on efforts to improve financial literacy through savings awareness among children in Ndeskati Village. The background of this research is based on the low understanding of children about the importance of saving and the lack of age-appropriate financial education facilities. The research method employed is a qualitative approach involving observation, interviews, and direct practice of saving activities through a simple program. The findings show that children begin to understand the concept of saving not only as storing money but also as a step toward achieving future goals. Furthermore, the active participation of parents and mentors plays an important role in building consistent saving habits. Through this financial literacy program based on savings awareness, it is expected to create a generation that is disciplined, responsible, and capable of managing finances properly from an early age.